POLUSI DALAM PERSPEKTIF AL-QUR’AN - Djaenab Djaenab (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
Humanity and the environment have a positive relationship. If humans treat the environment on the basis of trust, of course it will have an impact on environmental sustainability and a sustainable environment that will always benefit human life. Overcoming challenges that do not support the environment, will divert challenges to the entire community, including the order of life for mankind. Pollution in the Qur'an is not found concretely, but it is very clear, what is meant by the word fasada for all forms of derivation which implies destructive and destructive, both biological, physical and socio-cultural environments. Environmental damage can be caused by factors that affect the material that forms are substances that enter the environment and changes in their existence and factors that affect immaterial are other human behavior related to other people and their environment, both individuals and individuals who are interrelated.